Penerapan Model Pembelajara RADEC Terhadap Peningkatan Berpikir Kritis Perserta Didik Kelas V Pada Mata Pelajaran Matematika - Karimah, Shabrina Nida; Alamsyah, Trian Pamungkas; Pamungkas, Aan Subhan (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2024)
The critical thinking ability of learners in mathematical learning is essential. The study aims to know the increased critical thinking ability of learners in math by applying the RADEC learning model. The study is a quantitative study, using experimental methods and noninvasive control design. Studies were carried out on the school of class 5 SDIT Alia Nurul Jihadi. The sample used in this study numbered 51 trainees, 26 experimental classes I and 25 experimental classes II. The instrument used is a test of critical thinking ability performed at two stages of pre-test and post-test. Data processing was analyzed using statistical paramilitary test with test-t. The end result of research with different test results using test-t  (2.165) >  (2.01), where h₀ is rejected and h₁ is accepted. Research has concluded that the critical thinking ability of learners increased with the application of RADEC learning models to learners.